2016
DOI: 10.5194/acp-16-5021-2016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of VLT/X-shooter OH and O<sub>2</sub> rotational temperatures with consideration of TIMED/SABER emission and temperature profiles

Abstract: Rotational temperatures T rot derived from lines of the same OH band are an important method to study the dynamics and long-term trends in the mesopause region near 87 km. To measure realistic temperatures, the rotational level populations have to be in local thermodynamic equilibrium (LTE). However, this might not be fulfilled, especially at high emission altitudes. In order to quantify possible non-LTE contributions to the OH T rot as a function of the upper vibrational level v ′ , we studied a sample of 343… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
61
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 87 publications
(276 reference statements)
11
61
1
Order By: Relevance
“…The GRIPS 9 data were taken with a one-minute resolution, from which I computed a nightly mean temperature. This is similar to the data shown in Noll et al (2016), justifying this simplification of a…”
supporting
confidence: 78%
“…The GRIPS 9 data were taken with a one-minute resolution, from which I computed a nightly mean temperature. This is similar to the data shown in Noll et al (2016), justifying this simplification of a…”
supporting
confidence: 78%
“…Figures 3 and 4 while OH (5, 3) and (4, 2) band emissions are mainly collected at 1.6 µm (Baker et al, 2007). As OH emissions from different υ peak at different heights (von Savigny, 2015;Noll et al, 2016), the difference in OH 2.0 and 1.6 µm emission peaks is observed. Generally, the 2.0 µm emission peak lies above that of the 1.6 µm channel by ∼ 1.6 km at about 89 ± 2 km, thereby resulting in different values of two OHequivalent temperatures.…”
Section: Oh-equivalent Temperatures From Saber Kinetic Temperature Prmentioning
confidence: 93%
“…The work of von Savigny et al (2012a) showed that the peak altitude difference increases by 0.6 km per increasing vibrational level, assuming linear dependence. Noll et al (2016) reported shifts of 0.4 km for adjacent levels. Therefore, there should be offsets of roughly +1 and −1.5 km between the peak altitude in SATI and in SABER 1.6 and 2.0 µm channels, respectively.…”
Section: Sabermentioning
confidence: 99%